2005
DOI: 10.1097/01.brs.0000155415.89974.d3
|View full text |Cite
|
Sign up to set email alerts
|

Results of Long-Term Follow-Up in Patients Undergoing Anterior Screw Fixation for Type II and Rostral Type III Odontoid Fractures

Abstract: In our series, anterior odontoid screw fixation comprised a safe therapeutic modality with high stability and low mechanical failure rates during short-term and long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 58 publications
1
50
1
5
Order By: Relevance
“…But 35% judged their outcome as moderate or poor and 20% assumed that they would need additional treatment for their neck condition in the future. In contrast, in literature the results of various treatment modalities for C2-fractures, particularly for odontoid fractures, were frequently recognized as 'good' if not 'excellent' [25,62,72]. In the past, detailed data have been sparse commonly not exceeding cross-sectional assessments and despite the prevailing opinion that overall outcome was favourable, long-term analysis identified persisting symptoms of pain and stiffness in a meaningful number of patients [1,11,57,76].…”
Section: Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…But 35% judged their outcome as moderate or poor and 20% assumed that they would need additional treatment for their neck condition in the future. In contrast, in literature the results of various treatment modalities for C2-fractures, particularly for odontoid fractures, were frequently recognized as 'good' if not 'excellent' [25,62,72]. In the past, detailed data have been sparse commonly not exceeding cross-sectional assessments and despite the prevailing opinion that overall outcome was favourable, long-term analysis identified persisting symptoms of pain and stiffness in a meaningful number of patients [1,11,57,76].…”
Section: Clinical Outcomementioning
confidence: 99%
“…In normals the C1-2 joints are responsible for up to 60% of total neck rotation equaling 30°-45° [16,25,58,64,73]. Even though the osseus contour of the lateral C1-2 joints looks concave on radiographs, the padding of joint cartilage converts the articulating surfaces to biconvex discs [58] with the cartilage cover averaging 1.5-2 mm [48,51].…”
Section: Functional Outcome and Atlantoaxial Rotationmentioning
confidence: 99%
“…The impact of patients' age at index surgery on outcome was discussed controversially. While it was shown to have significant impact on union rates in several studies [6][7][8][9][10]30], other authors did not find a significant correlation between age and union rates [15,18,20,31]. Besides age, the number of screws used for AOSF might have significant impact on union rates, too.…”
Section: Introductionmentioning
confidence: 99%
“…First described by Bohler [13], several studies also reported on technical details, surgical outcomes and complications [2,6,[14][15][16][17][18][19][20][21][22][23][24][25]. AOSF allows osteosynthesis of reduced OF through a non-traumatic standardized surgical approach if compared to the posterior approach [26] and can preserve atlantoaxial motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation